Supply and command: a study of the late Roman commissariat - McCunn, Stuart (2018)
The Roman ability to project their power and defend their empire was based on the empire having the capability to maintain a standing army. This thesis is an examination of the commissariat that supplied this army since without logistical support such an army could not survive. The basic question under consideration is how well the commissariat functioned in late antiquity, the period when it was in its most developed and best documented state. When considering the commissariat of late antiquity it is important to understand what came before and how this system came into being. Of particular importance is the office of praetorian prefect, which went from being an imperial deputy with both military and judicial functions during the Principate to the chief administrative office in the late Roman state. Once this question has been addressed it is possible to look at the late Roman commissariat. The process of supply had several different stages, from raising supplies to their storage, transport, and distribution. All of these elements must be addressed separately. The system of supply in late antiquity was not static and there were several modifications to the system over the three centuries covered, most notably the creation of new positions at the top of the supply system. Determining the quality of the commissariat from this requires contrasting the twin considerations of effectiveness and efficiency – the ability to reliably provide supplies for the army and the expenditure of the minimum amount of resources necessary towards that goal. The detailed analysis provided in this thesis supports the conclusion that the late Roman army was, in general, effectively supplied. The issue of efficiency is more difficult to assess, but it is clear that there were many areas of great inefficiency within the Roman system. This in turn implies that the emperors prioritized effectiveness over efficiency – a conclusion consistent with the importance of the army to the emperors’ position.